Effects of Tamsulosin Combined With Solifenacin on Lower Urinary Tract Symptoms: Evidence From a Systematic Review, Meta-Analysis, and Trial Sequential Analysis of Randomized Controlled Trials - Song, Yuxuan; Chen, Guangyuan; Huang, Peng; Hu, Cong; Liu, Xiaoqiang (Frontiers in Pharmacology, 2020)
This study is aimed to systematically evaluate the efficacy of tamsulosin combined with solifenacin and provide clinical evidence for treatment of benign prostatic hyperplasia (BPH) with lower urinary tract symptoms (LUTS). PubMed, Cochrane Library, EMBASE, China National Knowledge Infrastructure, Chinese Biomedical Literature Database and Wanfang data information service platform were searched to select randomized controlled trials (RCTs) of tamsulosin combined with solifenacin in the treatment of BPH with LUTS. After extraction of the data, the statistical information was calculated by means of STATA 12.0. The publication bias was calculated using Egger’s test and Begg’s funnel plot. A total of 17 articles contained 1870 patients treated with tamsulosin in combination with solifenacin and 1897 patients treated with tamsulosin only were included in this study. Results show that tamsulosin combined with solifenacin therapy was more effective in reducing the Total International Prostate Symptom Score (TIPSS), Storage International Prostate Symptom Score (SIPSS), Quality of life (QOL) and Overactive bladder symptom score (OABSS) in comparison with tamsulosin monotherapy treatment. However, it was found that the combination therapy may increase levels of prostate-specific antigen (PSA) and the maximal urinary flow rate (QMAX). Differences between the combination therapy and tamsulosin monotherapy were not statistically significant for urgency episodes per 24h, micturitions per 24h, Voiding International Prostate Symptom Score (VIPSS) and postvoid residual volume (PVR). Tamsulosin combined with solifenacin therapy is more effective than tamsulosin monotherapy for the treatment of BPH concurrent with LUTS and won’t increase the risk of dysuria.